IMPLEMENTASI SISTEM INFORMASI SURAT MASUK DAN KELUAR TERSTRUKTUR PADA BAWASLU KABUPATEN SERANG - Rohman, Ali (Jurnal Ilmiah Sistem Informasi, 2024)
Correspondence is one of the most important things and is often done by every government agency, organization and office. It is still very rare for offices to process incoming and outgoing letters using virtual storage media, even though in the case of making the letter they already use a computer, but in terms of storing it is still done manually, it has not been stored computerized so that it will be very difficult, especially when searching for mail data that has been processed. pass. And not only in terms of storage that is carried out by the system with a computerized system, there are many other things that are very easy to do, including the approval process or letter signing which will be carried out in a structured manner, both incoming and outgoing letters. Because with the manual system the approval process will be complicated both time and effort. Based on the identification of this research, namely the implementation of the Incoming and Outgoing Mail Information System at the Bawaslu of Serang Regency based on a desktop using a qualitative research method with grounded research